Spore Germination for Three Edible Zimbabwean Mushrooms Using Biostimulants - Pamire , Melody; Parawira, Wilson (Tanzania Journal of Science, 2020)
Spores play critical roles in the population and community development of ectomycorrhizal fungi (EMF), which grow naturally in the presence of host plants. EMFs have not been cultivated commercially in most countries including those in Africa. In vitro germination of their spores is refractory and has been witnessed only in the presence of stimulants. In this study, germination of spores for three wild ectomycorrhizal fungi commonly collected in Zimbabwe was investigated under the influence of three biostimulants in Murashige and Skoog (MS) and Potato Dextrose Agar (PDA) media for the first time. The stimulatory capacity of tomato or potato roots or Saccharomyces cerevisiae was investigated for Amanita loosi, Cantharellus cibarius and C. miomboensis. MS and PDA were used as basal media and each had 1.5% activated charcoal. The experiment was in a factorial design: 3*3*2 and each treatment had five replicates. Spore germination and germ tube elongation were determined every 14 days until 120 days after inoculation. Overall, in the three fungi the tomato root resulted in a germ tube length of 78 µm compared to 61.4 µm and 51.33 µm from potato root and S. cerevisiae, respectively. There was no significant difference in the germ tube lengths from the three ECMs. There was also no significant interaction in germ tube length between the three factors. It was concluded that biostimulants can activate spore germination in the three indigenous mushrooms. However, there is need for more research to optimise the germination of the wild mushrooms using these biostimulants.